2022
DOI: 10.1177/1098612x211070988
|View full text |Cite
|
Sign up to set email alerts
|

Online survey to determine client perceptions of feline chronic lower airway disease management: response to therapy, side effects and challenges encountered

Abstract: Objectives The first aim of this survey was to report client experiences associated with the administration of common medications, particularly glucocorticoids and bronchodilators, in managing cats with feline lower airway disease (FLAD). The second aim was to ascertain client perception of response to treatment and level of satisfaction. Methods This was a prospective cross-sectional study. An online survey was distributed worldwide to cat owners caring for cats with a chronic cough. Only cats reported to hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 27 publications
(46 reference statements)
0
14
0
Order By: Relevance
“…Following the research ethics, respondents were provided with all the study information, including the study purposes and the use of the study for academic purposes only on the first page of the survey (Brown et al, 2022). Student participation was on a voluntary basis with information on the confidentiality of their participation and an option to withdraw from the survey any time before they submitted it (Paulin et al, 2022). No monetary rewards were provided for the respondents (Sousa et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Following the research ethics, respondents were provided with all the study information, including the study purposes and the use of the study for academic purposes only on the first page of the survey (Brown et al, 2022). Student participation was on a voluntary basis with information on the confidentiality of their participation and an option to withdraw from the survey any time before they submitted it (Paulin et al, 2022). No monetary rewards were provided for the respondents (Sousa et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…bronchitis, etc. In cats, the most important clinical signs associated to all these diseases are related to bronchoconstriction (BC) and include cough, dyspnea, and tachypnea [10,11]. Barometric whole-body plethysmography (BWBP) is a noninvasive lung function test that allows to demonstrate a BC status in cats.…”
Section: Introductionmentioning
confidence: 99%
“…Several retrospective studies have shown beneficial aspects of different medications on clinical signs in FLAD [1,6,8,18]. So far, however, variations in response to treatment have not been evaluated for both conditions separately [19], and research evaluating efficacy of drugs mainly focused on cats with experimentally induced asthma [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…As lifelong treatment is necessary in most cases, owner communication and satisfaction are important factors 9 19 . About one third of patients with FBD in the present study showed persistent clinical signs despite appropriate treatment, which is comparable to the data reported in another publication 46 .…”
Section: Discussionmentioning
confidence: 99%